Pengaruh Perbedaan Transportasi Sistem M-CLOVE dengan Konvensional dan Jenis Kelamin terhadap Respon Fisiologis Ayam Broiler - Pratama, T. A. I. P.; Yani, A.; Afnan, R. (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2016)
Meat consumption in Indonesia has increased with most needs come from broiler  meat.  However,  it  is  not  followed  by  development  of the  transportation technology that consider animal welfare. The purpose of this study was to compare the level of broiler stress measured from comb, shank and rectal temperature among sex between conventional transport system and environmentally transportation M- CLOVE. The results showed average of temperature and relative humidity during the transport process in the M-CLOVE was lower compared to the open crate. Temperature differences occured 1.4 °C with a relative humidity of 2.5% different. M-CLOVE transport reduced the level of stress of broiler which was indicated from lower comb temperature, shank temperature and rectal temperature which compared to broiler transported in open crate. Closed system and constant air circulation in the M-CLOVE  might  reduce  the  effects  of  heat  generated  from  exposure  to  direct sunlight during the transportation process.